Single shot trajectory design for region‐specific imaging using linear and nonlinear magnetic encoding fields. Issue 3 (5th October 2012) - Layton, Kelvin J.; Gallichan, Daniel; Testud, Frederik; Cocosco, Chris A.; Welz, Anna M.; Barmet, Christoph; Pruessmann, Klaas P.; Hennig, Jürgen; Zaitsev, Maxim
<x xml:space="preserve">Abstract</x> It has recently been demonstrated that nonlinear encoding fields result in a spatially varying resolution. This work develops an automated procedure to design single‐shot trajectories that create a local resolution improvement in a region of interest. The technique is based on the design of optimized local k‐space trajectories and can be applied to arbitrary hardware configurations that employ any number of linear and nonlinear encoding fields. The trajectories designed in this work are tested with the currently available hardware setup consisting of three standard linear gradients and two quadrupolar encoding fields generated from a custom‐built gradient insert. A field camera is used to measure the actual encoding trajectories up to third‐order terms, enabling accurate reconstructions of these demanding single‐shot trajectories, although the eddy current and concomitant field terms of the gradient insert have not been completely characterized. The local resolution improvement is demonstrated in phantom and in vivo experiments. Magn Reson Med 70:684–696, 2013. © 2012 Wiley Periodicals, Inc.